Passing the spear : a grounded theory study of the influence of family business value sets on succession planning in black family-owned businesses - Musengi, Sandra (Rhodes University, Faculty of Commerce, Department of Management, 2007)
Literature suggests that a small number of family businesses are able to make the transition from the founder to other family members with a common reason cited being the lack of planning. This study aims to build understanding of leadership succession in family businesses by focusing on the influence of a founder's family business value set on the succession planning process in Black family-owned businesses. Using the Strauss and Corbin (1990) grounded theory method, this study develops a theory of succession planning of Black familyowned businesses labelled Passing the Spear which is comprised of three stages based on an analysis of 21 qualitative interviews. The Spear was an analogy used to represent both the values of the founder and the family business, thus in Passing the Spear, founders where essentially performing a dual transfer of their values and leadership to the successor. The implementation of the process Passing the Spear was influenced by the family business value set of the founder, which in this study, were labelled as Traditional, Progressive, and Transitional. These value sets were distinguished by their behaviour regarding their choice of successor where founders with a traditional value set exhibited gatekeeping behaviour, while the behaviour of founders with a progressive value set was labelled navigating, and finally, founders with a transitional value set demonstrated behaviour labelled exploring. Furthermore, it was found that after the successor had been chosen, founders appeared to follow a generic succession planning process, however, the ease and timing of implementation was influenced by the family business context, evidence of being proactive and the degree of family business resilience. The process of Passing the Spear comprised of three stages of (a) Showing the spear where the founder's focus is on the induction and socialization of the successor using the strategies of bringing the successor into the family business and managing the family-business interface using relationships; (b) Explaining the spear entailed founders using the strategies of sharing knowledge and teaching the successors about the family business; and ( c) Sharing the spear was where founders focused on empowering the successors by implementing strategies of sharing responsibilities and learning from the successor.The process provides insights into the influence of family business values on the succession planning process and can be useful for founders of Black family-owned businesses in planning for succession in their businesses. In addition, the study provides another perspective of succession planning and offers a contribution to the literature for understanding succession in Black family-owned businesses.
Keywords: Grounded theory; Family-owned business enterprises; Family-owned business enterprises -- Succession; Family-owned business enterprises -- Management; Business enterprises, Black; Business planning